2021
DOI: 10.3390/cryst11101153
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties and SAR for Gadolinium-Doped Iron Oxide Nanoparticles Prepared by Hydrothermal Method

Abstract: This study is an attempt to produce gadolinium-doped iron oxide nanoparticles for the purpose of utilization in magnetic fluid hyperthermia (MFH). Six gadolinium-doped iron oxide samples with varying gadolinium contents ( were prepared using the hydrothermal method and high vapor pressure to incorporate gadolinium ions in the iron oxide structure. The samples were indexed as , with varying from 0.0 to 0.1. The results reveal that gadolinium ions have a low solubility limit in the iron oxide lattice (x = 0.04).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…31,32 From the spherulite nature of the micrographs, it is evident that β-phase formation in PVGF2.5 and PVGF5 is due to the interaction between the Gd-doped hematite and the CH 2 –CF 2 moiety of the PVDF polymer chain. 31,33…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 From the spherulite nature of the micrographs, it is evident that β-phase formation in PVGF2.5 and PVGF5 is due to the interaction between the Gd-doped hematite and the CH 2 –CF 2 moiety of the PVDF polymer chain. 31,33…”
Section: Resultsmentioning
confidence: 99%
“…31,32 From the spherulite nature of the micrographs, it is evident that b-phase formation in PVGF2.5 and PVGF5 is due to the interaction between the Gd-doped hematite and the CH 2 -CF 2 moiety of the PVDF polymer chain. 31,33 Elemental composition analysis was performed with EDS which depicts the stoichiometric ratio of Fe, O, and Gd in the doped hematite NPs. It was found that Gd showed 3.25 wt% instead of 5% doping in the nanocomposite due to improper attachment of some Gd 3+ ions in the hematite NPs and these were washed out by centrifugation [Fig.…”
Section: (C)] It Was Observed That Duementioning
confidence: 99%
“…Recently, nanoferrites have demonstrated technological advances in various applications including magnetic resonance imaging [1], magnetic fluid hyperthermia, targeted drug delivery, medical diagnosis [2], high-density magnetic recording, data storage devices, microwave devices, and magnetic fluid [3][4][5]. Therefore, nanostructured spinel ferrite, compared to their bulk counterparts, have attracted a lot of interest in different applications thanks to its remarkable mechanical, optical, magnetic and electrical properties [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Iron oxide nanoparticles (IONPs) can be useful in applications such as magnetic resonance imaging contrast agents and biosensors and in various biomedical fields, such as hyperthermia treatment, drug delivery, cancer targeting, transfection, cell tracking, and tissue repair, owing to their low toxicity, unique magnetic properties, and facile surface modification [1][2][3][4][5][6]. To use IONPs for bio-applications, the IONPs should have excellent colloidal stability, functionalization with biomolecules, and non-toxicity under physiological conditions [7].…”
Section: Introductionmentioning
confidence: 99%